Clinical characteristics of and antibody response to spotted fever group rickettsial infections in South India: Case series and serological cohort study. Issue 12 (12th October 2021) - Schmidt, Wolf‐Peter; Devamani, Carol S.; Elangovan, Divyaa; Alexander, Neal; Rose, Winsley; Prakash, John A. J.
Abstract: Objective: The clinical and serological characteristics of spotted fever group rickettsial (SFGR) infections in South Asia are poorly understood. We studied the clinical presentation and the IgM/IgG response in cases enrolled at two health care centres in South India. Method: We enrolled 77 patients. Fifty‐seven of these patients were recruited at a tertiary care centre, the remaining 20 at a community hospital (secondary care level). Diagnostic tests included IgM and IgG enzyme‐linked immunosorbent assay and polymerase chain reaction. Over a period of 1 year, 41 cases were followed up for repeated sero‐analysis. Results: Median age was 9 years (range 1–79). A rash was present in 74% of cases (57/77). In cases aged <15 years, rash was present in 94% (44/47) vs. 43% (13/30) in cases aged ≥15 years. An eschar was found in two cases (3%). Severe infection or complications occurred in 10 cases (13%). These included central nervous system infection (6/77, 8%), kidney injury (3/77, 4%), shock (3/77, 4%), lung involvement (2/77, 3%) and peripheral gangrene (2/77, 3%). IgM antibody levels increased faster after fever onset than IgG antibodies, peaking at 50 and 60 days, respectively. After the peak, IgM and IgG levels showed a slow decline over one year with less than 50% of cases showing persistent IgG antibody levels. Conclusion: Spotted fever group rickettsial infections in South India may be under‐diagnosed, as many cases may not develop a rash. The proportion of cases developing severe infection seems lower than for scrub typhus in this region. IgG seroprevalence may substantially underestimate the proportion in a population with past SFGR infection.